THE CHEMICAL ANALYSIS OF HAIRY COCKLE (Anadara antiquata)MEAT - Septin Alvin Mendrofa; Rahman Karnila; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Shellfish is one of the mollusks from the class of Bivalve or Pelecypods. Generally, shellfish body parts are divided into five body parts that are foot byssus, head, visceral mass, mantle and shell. The used shellfish in this research was a hairy cockle that was potential as an alternative food source. The purpose of this research was to determine the chemical content of hairy cockle meat. The used method was the experimental method with two stages consisting of the preparation of hairy cockle and the chemical analysis (moisture, ash, fat, and protein) of hairy cockle meat. Based on the results  showedthat the hairy cockle meat had nutritional content that was 79% moisture, 1.94% ash, the protein of 9.56%, and the fat of 8.66%. Keywords: Experiment, chemical content, hairy cockle (Anadara antiquata)